Barriers and facilitators for the inclusion of fertility care in reproductive health policies in Africa: a qualitative evidence synthesis. (9th December 2021) - Afferri, Anna; Allen, Haddijatou; Booth, Andrew; Dierickx, Susan; Pacey, Allan; Balen, Julie
Abstract: BACKGROUND: Infertility affects over 50 million couples worldwide and impacts people's social and emotional wellbeing. In low- and middle-income countries, particularly across Africa, the inclusion of fertility care into reproductive health (RH) policies remains fragmented or non-existent. OBJECTIVE AND RATIONALE: This review aims to provide a framework for understanding the inclusion (or lack thereof) of fertility care in RH policies in African settings. It synthesizes the barriers and facilitators to such inclusion, with a view to uncovering the positioning of fertility care in broader health systems and on the agendas of key stakeholders such as health policymakers and practitioners. SEARCH METHODS: A qualitative evidence synthesis was performed, systematically searching papers and grey literature. Searches were conducted in MEDLINE, EMBASE, CINAHL, Web of Science and Scopus between February and April 2020. No date restrictions were applied. Language was limited to publications written in English and French. Two reviewers independently screened titles and abstracts, and extracted data, applying thematic coding. The quality of the included papers was evaluated using The Joanna Briggs Institute Checklist for Text and Opinion Papers. OUTCOMES: The search identified 744 papers, of which 20 were included. Findings were organized under four cross-cutting categories, namely: perceived importance of infertility; influence of policy context; resource availability and access; and perceived quality of care. Across these categories, key barriers to the inclusion of fertility care in RH policies were limited political commitment, under-recognition of the burden of infertility and high costs associated with ART. Conversely, facilitators comprised specialized training on infertility for healthcare providers, standard procedures for ART safety and guidelines and North–South/South–South collaborations. WIDER IMPLICATIONS: The inclusion of fertility care in African RH policies depends upon factors that include the recognition of infertility as a disease, strong political engagement and proactivity and affordability of ART through opportunities for partnership with the private sector, which ease costs on the public health system. Further qualitative and quantitative research, including context-specific analysis and in-depth comparative approaches across diverse African countries, will help to delineate differential impacts of local and global factors on fertility care to address this neglected RH issue.